Potensi senyawa 4-Hidroksikalkon sebagai agen tabir surya - Hana Anisa Fatimi; Abdul Karim Zulkarnain; Marlyn Dian Laksitorini (STIKes Surya Global Yogyakarta, 2023)
4-Hydroxychalcone contains chromophore groups that can absorb UV light in such a way so that the compound can potentially be developed as a sunscreen. The objective of this study is to determine the optimum gel formula, evaluate the physical stability of 4-hydroxychalcone gel, and evaluate the activity of 4-hydroxychalcone gel as a sunscreen through in vitro tests. The method to determine the optimum formula is using Simplex Lattice Design (SLD) with Design Expert software version 10. The test for 4-hydroxychalcone gel activity is Sun Protecting Factor (SPF), percent of erythema transmission, and percent of pigmentation transmission with spectrophotometry method. The data were analyzed using SPSS version 25. The result of the research showed that the optimum formula for 4-hydroxychalcone gel consist of 1.5% HPMC, 1.8% CMC-Na and 0.6% methylcellulose has pH of 6.96; viscosity of 89.10 dpa.s; spreadability of 16.30 cm2; SPF value of 22.29; %TE value of 1.19% and %TP value of 0%. The base and 4-hydroxychalcone gel were stable to pH response but unstable to the viscosity and spreadability response for 6 weeks of storage at room temperature. 4-hydroxychalcone sunscreen has the potential as a photoprotective agent in vitro.